Place of Angioplasty for Coronary Artery Anomalies With Interarterial Course - Aubry, Pierre; Halna du Fretay, Xavier; Boudvillain, Olivier; Degrell, Philippe; , The ANOCOR Working Group (Frontiers in Cardiovascular Medicine, 2021)
Few patients with an anomalous aortic origin of a coronary artery (AAOCA) require a correction of the congenital anomaly. Current recommendations offer surgical repair in first line therapy with a prevention of sudden cardiac death as main objective. However these guidelines are focused on children and not based on randomized controlled studies. Furthermore decision-making must be different in an adult population less exposed to the risk of sudden cardiac death. Current practices showed unwillingness to offer a surgical treatment for right AAOCA associated with ischemic symptoms or myocardial ischemia. We sought in the review to explain the rational for percutaneous coronary intervention in right AAOCA with interarterial course and to present the published results of this technique.